In Search of Development: Zimbabwe Exemplar From 2000 to 2015 - Kabonga, Itai; Marime, Rodwell (Africanus: Journal of Development Studies, 2017)
The period 2000 to 2015 epitomised Zimbabwe’s relentless search for development as patronised by major policies that were meant to spur socio-economic development. Using a synthesis of qualitative collection methods – such as key informant interviews, in depth interviews and documentary analysis, the article interrogates and evaluate the impact of the Fast Track Land Reform Programme (FTLRP), Reserve Bank of Zimbabwe (RBZ) quasifiscal activities, Indigenization and Economic Empowerment drive, as well as the Zimbabwe Agenda for Sustainable Socio-Economic Transformation (ZIMASSET) on the trajectory of development. This period portrayed Zimbabwe as a country of contradictions, ambivalence and contestations. The article unequivocally argues that development policies in Zimbabwe were formulated by government as a reaction to political threats – and that for Zimbabwe to achieve its development goals, policies should not be a reaction to political threats; but genuine action by government to improve the living conditions of the people.